The Effect Of Health Education On Princess Adolescent Anniversary In Dealing With Menache - Siringoringo, Edison; Selviani; Nurlina (Jurnal Life Birth, 2020)
Anxiety is a state of mood marked by negative effects and symptoms of physical tension symptoms in which a person anticipates the possibility of danger or misfortune in the future with feelings of worry, anxiety may involve feelings, behaviors, and physiological responses. The aim is to determine the effect of health education on the level of anxiety of young women in dealing with menarche in Smp Negeri 9 Bulukumba. The method used in this study is to use a pre-experiment approach to post-test control group design. Without using a control group. The study is to use a pre-experimental design with a pro-test post-test control group design approach without using a control group. The result of this study is based on the results of statistical tests with Mc Nemar hypothesis test with a significance level of 95% obtained P-value = 0,000 (p<0,05), So Ha is accepted then it can be stated there is an influence of health education on the level of anxiety of young women in dealing with menarche in Smp Negeri 9 Bulukumba. Conclusions and suggestions there is the influence of health education on the level of anxiety of young women in dealing with menarche in-state junior high school 9 Bulukumba in 2019.